Pendekatan Komprehensif Berbasis Al-Qur'an dan Hadits dalam Pengembangan Pendidikan Islam: Integrasi Nilai, Metode, Evaluasi, Sosio-Kultural, dan Kompetensi Pendidik - Siti Hanifah Parawansah; Ainur Rofiq Sofa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines a comprehensive approach based on the Qur'an and Hadith in developing Islamic education, focusing on value integration, methods, evaluation, socio-cultural contexts, and educator competencies. Using a literature review method, it highlights the importance of Islamic values such as moral education, ethics, knowledge, and teaching based on compassion and patience in building a holistic education system. Implementation includes Islamic curricula, participatory methods, and comprehensive evaluations covering cognitive, affective, and psychomotor domains. Challenges include cognitive-dominated curricula, socio-cultural differences, and educator quality. Adaptive and collaborative approaches are recommended to address these issues, enhancing educator competencies and aligning teaching methods with modern needs. Holistic and relevant Islamic education can balance spiritual, intellectual, and social dimensions, producing virtuous, knowledgeable, and socially contributive generations. This approach ensures Islamic education remains relevant without losing its essence amidst global changes.